Odpowiedzi

2009-10-24T11:20:33+02:00
1. x²-4+3x-21= 2 - x²-1
2. x²-1÷4-x²+1:2=-x²:4
2009-10-24T11:31:41+02:00
-( x-2)² + 3( x - 7) = 2 - ( x+1)( x-1)
-(x²+4-4x)+3x-21=2-(x²-1)
-x²-4+4x+3x-21=2-x²+1
-x²+7x+x²=4+21+2+1
7x=28/:7
x=4

drugi rozwiąż podobnie
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-10-24T11:59:04+02:00


1.-( x-2)² + 3( x - 7) = 2 - ( x+1)( x-1)
-(x2-4x+4)+3x-21=2-x2 -12
-x2+4x-4+3x-21=2-x2-1
-x2 +7x-25=1-x2
7x-25=1
7x=26



2.( x- 1)² : 4 - (x+1)² : 2 = -x² : 4
x2-2x+12:4-(x2 +2x+12):2=-x2 :4
x2 -2x+1:4-x2 -2x-1:2=-x2 :4
-4x+1:4-1:2=x2 :4
-4x+1/4-2/4=x2 :4
-4x-1/4=x2 :4